MENINGKATKAN KREATIVITAS ANAK USIA 5-6 TAHUN MELALUI KEGIATAN MEMBATIK ECOPRINT - Fitriah; Kaspul Anwar; Raoda Tul Jannah Maruddani; Amiroh; Jasna Febriani (LP2M IAIN Sultan Amai Gorontalo, 2025)
This study aims to enhance the creativity of 5-6 year-old children at Taman Kanak-Kanak Islam Ahsan in Jambi City through ecoprint batik activities using the Classroom Action Research (CAR) method. Based on observations conducted by the researcher from December 18-20, 2023, involving 16 children at TK Islam Ahsan, daily and weekly analyses indicated that 12 children had not shown adequate development in their creativity. Specifically, 75% of the children were categorized as